Inter-Provincial Spatial Linkages of Crime Pattern in Indonesia: Looking at Education and Economic Inequality Effects on Crime - Dian Trisnawati; Khoirunurrofik Khoirunurrofik (Indonesian Journal of Geography, 2019)
Crime is one of social issues and it becomes spatial phenomenon as the inclination of crime rate in a particular region affecting its neighboring regions. This paper aims to explore the inter-provincial spatial linkages of crime rate in Indonesia and examine the effects of lack of education and economic inequality on criminal occurrences.  Panel data of 33 provinces in Indonesia from 2007-2013 periods are explored and discover the existence of spatial linkages of crime rate among provinces. The spatial autocorrelation (SAC) model shows that the economic gap amid the society become the trigger for crime occurrence. Criminal actions are expected to increase as the Gini index is high since the inequality can make social jealousy is inevitable and triggering criminal actions. Furthermore, lack of education is also proven significantly in affecting crime rate, imply that education level may affect individual’s decision to commit criminal actions.